2006
DOI: 10.1021/jp057074n
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Aqueous Inorganic−Malonic Acid Particles:  Nucleation Rates, Dependence on Size, and Dependence on the Ammonium-to-Sulfate Ratio

Abstract: Using an electrodynamic balance, we determined the relative humidity (RH) at which aqueous inorganic-malonic acid particles crystallized, with ammonium sulfate ((NH(4))(2)SO(4)), letovicite ((NH(4))(3)H(SO(4))(2)), or ammonium bisulfate (NH(4)HSO(4)) as the inorganic component. The results for (NH(4))(2)SO(4)-malonic acid particles and (NH(4))(3)H(SO(4))(2)-malonic acid particles show that malonic acid decreases the crystallization RH of the inorganic particles by less than 7% RH when the dry malonic acid mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 59 publications
7
77
1
Order By: Relevance
“…Interactions between organic and inorganic components within an aerosol particle can influence DRH and ERH of inorganic salts or even totally suppress crystallization (Marcolli et al, 2004;Parsons et al, 2006). Furthermore, liquid-liquid phase separation (LLPS) into a mainly polar inorganic and a less polar organicrich phase during humidity cycles may occur (Marcolli and Krieger, 2006).…”
Section: Song Et Al: Liquid-liquid Phase Separation and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between organic and inorganic components within an aerosol particle can influence DRH and ERH of inorganic salts or even totally suppress crystallization (Marcolli et al, 2004;Parsons et al, 2006). Furthermore, liquid-liquid phase separation (LLPS) into a mainly polar inorganic and a less polar organicrich phase during humidity cycles may occur (Marcolli and Krieger, 2006).…”
Section: Song Et Al: Liquid-liquid Phase Separation and Morphologymentioning
confidence: 99%
“…Previous studies on phase transitions of single aerosol particles have mostly been performed with one organic substance in the presence of AS (Parsons et al, 2006;Ling and Chan, 2008;Ciobanu et al, 2009;Yeung et al, 2009;Bertram et al, 2011). Studies on more complex organic mixtures are needed to obtain insight into the phase transitions of organic/inorganic aerosols considering atmospheric aerosol composition.…”
Section: Song Et Al: Liquid-liquid Phase Separation and Morphologymentioning
confidence: 99%
“…Many studies on phase transitions of mixed organicinorganic salt particles of atmospheric relevance have focused on deliquescence and efflorescence (see for example Brooks et al, 2002Brooks et al, , 2003Choi and Chan, 2002;Chan and Chan, 2003;Wise et al, 2003;Braban and Abbatt, 2004;Pant et al, 2004;Parsons et al, 2004aParsons et al, , 2006Badger et al, 2006;Marcolli and Krieger, 2006;Salcedo, 2006;Ling and Chan, 2008;Treuel et al, 2009;Bertram et al, 2011;Smith et al, 2012). These studies have shown that when liquidliquid phase separation does not occur, the addition of organics to inorganic salts lowers the deliquescence and efflorescence relative humidities of the salts.…”
Section: Y You Et Al: Liquid-liquid Phase Separation In Particles Cmentioning
confidence: 99%
“…Zhang and Chan, 2000;Lee et al, 2008), hygroscopicity and phase transition (e.g. Tang and Munkelwitz, 1994;Choi and Chan, 2002;Li et al, 2005;Parsons et al, 2006;Pope et al, 2010a;Zobrist et al, 2011), measurement of vapour pressure (e.g. Pope et al, 2010b;Soonsin et al, 2010), oxidation chemistry (e.g.…”
Section: H-j Tong Et Al: a New Electrodynamic Balance (Edb) Designmentioning
confidence: 99%